Rural telephony: The mesh potato network - Song, Steve (Technical Centre for Agricultural and Rural Cooperation, 2008)
A group of software experts, technical specialists and telecommunications entrepreneurs in South Africa is working to develop an inexpensive system to provide rural and under-served area with affordable telephone communication.